(Intellectual) Property Rights on Cryptocurrency A comparison between the legal situation in South Africa and Germany - Papiernick, Maik (Department of Commercial Law, 2025)
In contrast to other applications that use blockchain (such as non-fungible tokens/NFTs or smart contracts, which I will not discuss), cryptocurrencies are the most widespread in society - and are already official currency in El Salvador, for example. Due to this new type of technology (blockchain), cryptocurrencies can hardly be categorised in existing legal categories. This is why it is also difficult to establish rights to cryptocurrencies. I would like to address this problem in my master's thesis: What (intellectual) property rights can there be to cryptocurrencies? Such rights could be necessary to protect the holder of cryptocurrencies. I will focus on two categories of rights in particular: Intellectual property rights and the private law understanding of property (which is usually on tangible things). At the beginning, I shed light on the technical background of cryptocurrencies and blockchain technology, explain the most important terms and present an example transaction. I then turn to the common generic term of intellectual property rights and private law property: property. First, I examine what is meant by property - first on a philosophical level, then on to the constitutional understanding and individual areas of law in South Africa and Germany. It is noticeable that there are already regulations on cryptocurrencies in some selected areas - but these do not necessarily allow any conclusions to be drawn as to whether (intellectual) property rights to cryptocurrencies exist. Therefore, I analyse the existing intellectual property rights (including copyright and database right) and also discuss a possible sui generis right to cryptocurrencies. Furthermore, I turn to an extension of the private law understanding of property in South Africa and Germany - in particular the question of whether things that fall under the private law understanding of property must necessarily be tangible (and if it is possible to change requirements for private law property in South Africa and Germany). After all, cryptocurrencies could be similar to tangible objects rather than intangible objects. Finally, I will briefly discuss other jurisdictions such as the USA, UK or Singapore with regard to the question of whether a (private law) property right to cryptocurrencies exists. I then summarise my findings in a conclusion.